Chemical and Functional Characteristics of Composite Flour based on Kind of the Modified Cassava Flour with Several Drying Methods and Wheat Flour - Rifyan Helmi; Ridwansyah Ridwansyah; Herla Rusmarilin (Universitas Sumatera Utara, 2015)
The research was aimed to study of the chemical and functional characteristics of composite flour from kind of the modified cassava flour with several drying methods and wheat flour. The reseach had been performed using completely random design (CRD) with two factors i.e the ratio of kind of modified cassava flour with four drying methods, i.e M1=sunlight, M2=solar dryers, M3=stove and M4=combination of solar dryers with stove, and the ratio of wheat flour and kind of modified cassava flour with several drying methods: i.e (T1= 90%:10% ; T2= 80%:20% ; T3= 70%:30% ; T4= 60%;40% ). Parameters analyzed were water content (%), ash content (%), fat content (%), protein content (%), dietary fiber content (%), water and oil absorption (g/g), swelling power (g/g) and baking expansion (ml/g). The results showed that the kinds of modified cassava flour with several drying methods had highly significant effect on protein content, beaking expansion, and had significant effect on the swelling power. Ratio of the flour showed highly significant effect on water content, fat content, protein content, dietary fiber content, water and oi labsorption, swelling power and baking expansion. Keyword : cassava flour, composite flour, wheat flour